Increasing Self-Confidence Through Public Speaking (Best Practice at HMPS MPI Period 2021-2022) - Heru Sulistya; Muhammad Ulil Abshor; Ahmad Zuhdan Makhluf (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
This research is based on the gap between what reality should be and the actual situation, namely related to public speaking abilities. This ability can be seen as an essential and valuable skill. In reality, there are still many students who do not understand the concept of public speaking and feel embarrassed when speaking in front of a public audience. This research aims to explore the urgency of public speaking and analyze the best practice of public speaking in increasing student self-confidence. This research used a quasi-experimental with a one-group pretest-posttest design, carried out by measuring the subject's understanding, providing treatment, and re-testing the research subjects. The research subjects were HMPS MPI 2021-2022 administrators, totaling 33 students. Primary data was obtained through pre-tests, and post-tests, and interviews, while secondary data was obtained through books, articles, and websites. The results of this research show that: 1) Public speaking is a very important skill for students because it can be used as preparation when returning to society; Train and increase self-confidence in facing the world of work, project presentations, and business negotiations; Improve your ability to express yourself well and be more appreciated. 2) Best practice as the best practice in increasing student self-confidence (HMPS MPI 2021/2022 Period) is carried out through Public Speaking Class training. The results of this training showed changes in the understanding of public speaking before and after the training, where 22 out of 33 students (66.67%) were in the